The demographic dividend in Bhutan taking advantage of transition. ([Manila] Asian Development Bank, 2019)
Bhutan is undergoing a rapid demographic transition as a result of higher life expectancy and literacy rates, and a steep reduction in fertility. The country has benefited economically from a higher proportion of working-age people. However, as the demographic transition continues the old-age population will increase, turning the demographic dividend into a demographic tax. Bhutan is halfway through the dividend phase and can use these opportunities to help prepare for population aging.
Keywords: Old age -- Economic aspects -- Bhutan; Electronic books